Identification of SLC22A5 Gene Mutation in a Family with Carnitine Uptake Defect. (5th May 2015) - Mutlu-Albayrak, Hatice; Bene, Judit; Oflaz, Mehmet Burhan; Tanyalçın, Tijen; Çaksen, Hüseyin; Melegh, Bela
Abstract : Primary systemic carnitine deficiency is caused by homozygous or compound heterozygous mutation in the SLC22A5 gene on chromosome 5q31. The most common presentations are in infancy and early childhood with either metabolic decompensation or cardiac and myopathic manifestations. We report a case of 9-year-old boy with dysmorphic appearance and hypertrophic cardiomyopathy. Tandem MS spectrometry analysis was compatible with carnitine uptake defect (CUD). His sister had died due to sudden infant death at 19 months. His second 4-year-old sister's echocardiographic examination revealed hypertrophic cardiomyopathy, also suffering from easy fatigability. Her tandem MS spectrometry analyses resulted in CUD. We sequenced all the exons of the SLC22A5 gene encoding the high affinity carnitine transporter OCTN2 in the DNA. And one new mutation (c.1427T>G → p.Leu476Arg) was found in the boy and his sister in homozygous form, leading to the synthesis of an altered protein which causes CUD. The parent's molecular diagnosis supported the carrier status. In order to explore the genetic background of the patient's dysmorphic appearance, an array-CGH analysis was performed that revealed nine copy number variations only. Here we report a novel SLC22A5 mutation with the novel hallmark of its association with dysmorphologic feature.